Genetic control over characteristic of 1000 seeds weight in hybrids of sugar beet and combining ability of crossbreeding components - М. О. Корнєєва; О. В. Ненька; М. М. Ненька (Plant Varieties Studying and Protection)
The article shows experimental data of interline hybrids of sugar beet on the basis of weight of 1000 seeds, genetic determination of characteristic based on the method of Hayman and topcrossed polytested crossbreeding is established, their comparison is made. It also highlights valuable hybrid combinations and valuable for combining pollinating lines used in the breeding to enhance properties of sowing seeds.